2011
DOI: 10.1177/201010581102000202
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Anaemia in Older Hospitalised Patients

Abstract: Introduction:We aim to investigate the prevalence and risk factors for anaemia among the elderly in a tertiary hospital. Methods:A retrospective study was conducted on 742 consecutive geriatric patients who were admitted to the medical unit of our hospital. The demographic and laboratory values for patients were examined. Anaemiarelated data were studied. Patients with no/missing demographical or laboratory data and those who passed away after admission were excluded.Results: There was a high prevalence of ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
4
10
1
2
Order By: Relevance
“…This finding closely corroborates to that of Ramachandra et al 13 Shavelle et al, and Tay et al, found equal number of male and female elderly anaemic cases in their study. 2,14 In another study by Choi et al the total number of elderly anaemic females were found to be more as compared to total number of males. 11 In our series, the mean haemoglobin level in the study geriatric population was 9.08±2.309 g/dl.…”
Section: Discussionmentioning
confidence: 94%
“…This finding closely corroborates to that of Ramachandra et al 13 Shavelle et al, and Tay et al, found equal number of male and female elderly anaemic cases in their study. 2,14 In another study by Choi et al the total number of elderly anaemic females were found to be more as compared to total number of males. 11 In our series, the mean haemoglobin level in the study geriatric population was 9.08±2.309 g/dl.…”
Section: Discussionmentioning
confidence: 94%
“…Evidences showed that anemia in elderly has been strongly linked with severe complications, including impaired physical functioning [ 10 ], decreased functionality [ 11 ], multidimensional loss of function [ 12 ], increased risk of frailty [ 13 15 ], depression [ 16 ], cognitive impairment [ 17 ], obstructive sleeping apnea [ 18 ], frequent comorbidity and hospitalization [ 19 21 ], and increased risk of death [ 20 , 22 , 23 ]. Despite old age being a major risk factor for anemia which threatens the quality of elderly life and has a substantial social and economic effects, anemia, however, should not be accepted as an inevitable consequence of aging, as it does reflect poor health and increased vulnerability to adverse outcomes in older persons [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dharmarajan et al found maximum number of cases anaemia in the age group 70-79 years 14 and Tay et al found maximum number of anaemia cases in the age group of 75-84 years. 15 Our study hence highlights that most of the anaemic elderly might have an underlying treatable cause for anaemia. It is essential to aware of the coexistence of anaemia in elderly, although the presenting manifestation may be for a different reason.…”
Section: Resultsmentioning
confidence: 66%